The Effect of Perceived Benefits and Satisfaction on Interest in Sustainable Use of Gopay's Digital Wallet: marketing Management - Chika Aninda Putri; Abdul Yusuf (Fakultas Bisnis, 2022)
This study aims to determine the effect of benefits and satisfaction on the interest in sustainable use of the GoPay digital wallet. The method used in this research is quantitative with a descriptive and verification approach. The sample used in this study was 384 using a sampling technique using non-probability sampling, namely purposive sampling. The data analysis technique used is analysis with partial and simultaneous hypothesis testing. testing is assisted by the SPSS tool. The result of this study is that there is a correlation between perceived benefits and satisfaction has a fairly strong relationship. Partially, perceived benefits have an effect of 12.9% and satisfaction has an effect of 12.6% on interest in use. Perceived benefits and satisfaction have a positive and significant effect on interest in sustainable use.